Determinant Analysis of Human Development Index in North Sumatra Province 2010-2021 - Luqiana, Nadia Imti; Utomo, Yuni Prihadi (Trunojoyo University of Madura, 2023)
The human development index (IPM) is an index that contains three essential dimensions in development, namely fulfilling the need for a long and healthy life, obtaining knowledge and being able to meet a decent standard of living. This study examines the factors influencing HDI in North Sumatra Province from 2010 to 2021. The HDI in North Sumatra Province continued to increase during the 2010-2021 period, but in 2020 HDI growth experienced a slowdown due to the COVID-19 pandemic resulting in a decrease in adjusted per capita expenditure. The analytical method used in this research is Ordinary Least Square (OLS) regression analysis. The results showed that government spending on education, government spending on health, gross regional domestic product and gender equality affected the human development index in North Sumatra province. Meanwhile, the Proportion of Female Workforce variable was found to not affect the Human Development Index variable in North Sumatra Province. This variable has no effect because most women work as housewives, and men are more economically active and more domiciled than women. Thus, the government is expected to further improve human resources quality through education and health, increasing the minimum wage for workers and reducing gender inequality.